New technologies for the Bundeswehr: Need for action due to technical innovations - Torben Arnold (Stiftung Wissenschaft und Politik (SWP), 2024)
As the demands on German foreign and security policy increase in a Europe characterised by multiple crises, so do the demands on the German armed forces. In order for the Bundeswehr to become more assertive and effective as a deterrent, despite limiting factors such as personnel and materiel shortages, it must be able to employ new technologies more quickly and extensively. The faster and more effectively these technologies are harnessed, the more advantages they will bring on the battlefield. The current political will for change, the pressure to adapt due to the evolved security situation and the increase in financial resources are creating an unprecedented momentum.
Keywords: 320; German foreign and security policy; Bundeswehr; personnel and materiel shortages; artificial intelligence (AI); unmanned systems; loitering munition